The Crisis Of Technocracy - Gareth Davies (Amsterdam Law Forum, 2009)
The European Union tries to be a responsible, technocratic, scientific regulator. As national governments struggle with populist calls for protectionism and state aid it preaches a co-ordinated, economically defensible recovery policy. Yet the paradox is that it was the experts who created the crisis, with complex systems and models that are now discredited. Does the solution really lie in more advice from the same people, or is the crisis also one of ideas, showing that we cannot understand or manage the world using only quantitative sciences, and human and political judgment still need to be central? Not only the EU, but also a technocratic model of government, is now facing a test. Success will bring great political capital for both, whereas failure will require a rethinking of the way we make rules, as well as of where we make them.